PJMHS 2021
DOI: 10.53350/pjmhs211571722
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence, Awareness Level and Attitude of Self-Medication Among Student Nurses

Abstract: Self-medication is an alternative for high cost medicines. Inappropriate practice of self-medication wastes resources, increases drug resistance, and poses a major health risk. The goal of this study was to look at nursing students' understanding, attitudes, and behavior about self-medication. This research was conducted among nursing students of mayo hospital of Pakistan in 2021. This survey comprised 301 student nurses in total. The students' knowledge, attitude, and behavior of self-medication were assessed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 6 publications
0
1
0
Order By: Relevance
“…According to Pourranjbar, Khodadadi [21], the pupils must be inspired to participate in sports because they significantly impact their psychological well-being and help them perform better. Meanwhile, Saddique, Safdar [61] reported that the awareness level of students has significant impact on their health management.…”
Section: Plos Onementioning
confidence: 99%
“…According to Pourranjbar, Khodadadi [21], the pupils must be inspired to participate in sports because they significantly impact their psychological well-being and help them perform better. Meanwhile, Saddique, Safdar [61] reported that the awareness level of students has significant impact on their health management.…”
Section: Plos Onementioning
confidence: 99%